PENGUATAN KOMPETENSI GURU MELALUI PELATIHAN MEDIA WORDWALL UNTUK PENINGKATAN PEMBELAJARAN DI SDN LADEN I PAMEKASAN - Hesti Kusumawati; Moh Khalid Hasan; Abdul Wafi; Sahril Hamdani (CV. Jendela Gagasan, 2025)
The background of this research is based on the importance of improving digital literacy and teachers' ability to utilize interactive learning media as a requirement for 21st-century learning. This study aims to describe the process of strengthening teacher competency through training in the use of Wordwall media and its impact on improving the quality of learning at SDN Laden 1 Pamekasan. This study uses a qualitative approach with a descriptive research type. Data were obtained through observation, interviews, and documentation, then analyzed through data reduction, data presentation, and conclusion drawing. The results of the study indicate that Wordwall media training can improve teachers' competency in digital knowledge and skills. This improvement is evident in the teachers' abilities, which initially were at a basic level, becoming more skilled in creating, adapting, and integrating various forms of quizzes and educational games into their lessons. Teachers demonstrated enthusiasm and readiness to implement Wordwall in teaching and learning activities, especially as an interesting and enjoyable evaluation medium for students. Furthermore, the use of Wordwall has a positive impact on the learning process, marked by increased student motivation, participation, and activeness during learning activities. The results of this study are expected to serve as a reference for other schools in developing learning technology training..